2020
DOI: 10.1186/s12917-020-02466-5
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fermented soybean meal replacement alleviates diarrhea in weaned piglets challenged with enterotoxigenic Escherichia coli K88 by modulating inflammatory cytokine levels and cecal microbiota composition

Abstract: Background: Impaired gut microbiota leads to pathogenic bacteria infection, pro-inflammatory response and postweaning diarrhea. Enterotoxigenic Escherichia coli (ETEC) K88 is a major cause of post-weaning diarrhea in weaned piglets. Fermented soybean meal (FSBM) could relieve diarrhea, alleviate inflammatory response, and modulate gut microbiota of weaned piglets. We used ETEC K88-challenged weaned piglet model to investigate the effects of FSBM on the growth performance, inflammatory response and cecal microb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 37 publications
4
28
0
1
Order By: Relevance
“…It has been reported that healthy pigs had a higher abundance of Prevotellaceae and Lachnospiraceae compared with diarrhoeic pigs [68]. Wang et al [69] also reported that the increased abundance of Prevotellaceae_NK3B31_group contributed to alleviate the diarrhea of weaned pigs challenged with enterotoxigenic Escherichia coli K88. In a mice model of ulcerative colitis, Prevotellaceae_UCG_001 has been shown to positively associated with anti-in ammatory cytokines (e.g.…”
Section: Discussionmentioning
confidence: 98%
“…It has been reported that healthy pigs had a higher abundance of Prevotellaceae and Lachnospiraceae compared with diarrhoeic pigs [68]. Wang et al [69] also reported that the increased abundance of Prevotellaceae_NK3B31_group contributed to alleviate the diarrhea of weaned pigs challenged with enterotoxigenic Escherichia coli K88. In a mice model of ulcerative colitis, Prevotellaceae_UCG_001 has been shown to positively associated with anti-in ammatory cytokines (e.g.…”
Section: Discussionmentioning
confidence: 98%
“…Prevotella has been recognized as the primary contributor to the metabolic network involving carbohydrate utilization and the production of SCFA [ 48 ] and has been negatively associated with Escherichia coli -induced enteric infection in the human colon [ 61 ]. Wang et al and Dou et al also reported that an increased abundance of Prevotellaceae_NK3B31_group helps to alleviate the occurrence of diarrhea in weaned pigs challenged with enterotoxigenic Escherichia coli K88 [ 62 , 63 ]. Ruminococcaceae is known to produce SCFAs by degrading various polysaccharides and fibers.…”
Section: Discussionmentioning
confidence: 99%
“…The probiotic effect and reduction of enteric pathogens is another benefit of the inclusion of FSBM in animal diets [ 6 , 8 , 9 , 21 ]. However, in the present study, the complete substitution of SBM by FSBM, though shown in vitro activity against ST, did not reduce ST cecal colonization in either the prophylactic or therapeutic models.…”
Section: Discussionmentioning
confidence: 99%
“…However, in recent years, the utilization of probiotic bacteria has also been used to reduce the anti-nutritional factors of soybean meal through fermentation methods. Several studies have demonstrated that the fermentation process increases the nutritional value [ 6 ], reduces intestinal inflammation [ 7 ], and minimizes colonization of enteric pathogens [ 8 , 9 ]. In the present study, a Lactobacillus salivarius and a Bacillus licheniformis strains isolated from poultry were used to ferment soybean meal.…”
Section: Introductionmentioning
confidence: 99%